2015
DOI: 10.4028/www.scientific.net/jera.19.112
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Fatal Accidents Involving Motorcycles in Low Income Region (Case Study of Karangasem Region, Bali-Indonesia)

Abstract: Karangasem region is the lowest income region in Bali Province-Indonesia. The people are highly dependent on using motorcycle for their daily movement. Karangasem has a high fatality rate of traffic accidents. There are 190 cases of the traffic accident and causing the death of 140 people. The number of accidents involving motorcycles are 172 cases. The objective of this study is to investigate factors that influence fatal traffic accidents involving motorcycles. This study used traffic accident data over 6 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 10 publications
0
6
0
2
Order By: Relevance
“…Low-income countries require solutions to a major public health problem that involve the use of motorcycles and its related challenges. Several studies indicate that low-income countries are affected by high motorcyclist traffic, bad road conditions, and road culture problems [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…Low-income countries require solutions to a major public health problem that involve the use of motorcycles and its related challenges. Several studies indicate that low-income countries are affected by high motorcyclist traffic, bad road conditions, and road culture problems [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…Dalam konferensi pers Indonesia Road Safety Award (IRSA) 2016 di Jakarta, Kepala Bagian Keamanan dan Keselamatan Korlantas Polri Kombes Indra Gautama, menjelaskan bahwa jumlah korban meninggal akibat kecelakaan lalu lintas saat ini jauh lebih tinggi dibandingkan korban meninggal akibat narkoba. Angka fatalitas korban meninggal dunia 26 ribu sekian, itu artinya sekitar 60-70 orang meninggal setiap hari akibat kecelakaan lalu lintas (Suthanaya 2016;Jusuf et al 2017), sedangkan narkoba hanya 40-50 sehari (Leechaianan & Longmire 2013). Hal ini berarti kecelakaan lalu lintas di Indonesia sudah harus menjadi prioritas.…”
Section: Pendahuluanunclassified
“…The predicted exponential growth of vehicles will be followed by rapid growth in oil demand and a significant increase in environmental impact such as air pollution, traffic noise, and road traffic accidents. By using traffic accident data in low-income regions (Karangasem regency in Bali province, Indonesia), [2] found that there were 172 accidents involving motorcycles. According to [3], more attention has been given to the adverse impact of road traffic noise on health in developing countries.…”
Section: Introductionmentioning
confidence: 99%